Cellular Effects of Wound Fluid (Seroma) from Tumor Bed on Human Breast Cancer Cell Lines: Seroma in breast cancer cell lines - Shahani, Minoo; Rouhollah, Fatemeh; Atabi, Fereshteh; Hajrasouliha, Shadi; Samsami, Majid (Archives of Advances in Biosciences, 2021)
Introduction: Post-lumpectomy wound fluid (seroma) contains many proteins from tumor bed due to physiologic answer to operation and wound healing process. Some cellular tests had been performed on different types of breast cancer (BC) cell lines and normal cell line while treated with seroma. Materials and Methods: The wound fluid samples were collected from BC patients. The human BC cell lines included MCF-7, MDA-MB-231 as well as normal non-tumorigenic epithelial cell line (MCF-10). Results: Seroma could inhibit various cancer cells proliferation pattern in comparison with the normal cell. Concerning the cell death, aggressive MDA-MB-231 cells were put into the apoptosis process. Besides, seroma could decrease colony count and size and changed the clone morphology from holoclone to paraclone. Regarding the invasion assay, seroma significantly inhibited cell motility. Conclusion: By remaining in tumor bed, seroma can induce inhibitory pattern of proliferation, and change the morphology of cancer cell colony and cell motility, consequently leading to positive impact on patients who suffer from cancer.